2014
DOI: 10.1002/jbmr.2355
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Splice Mutation in PLS3 Causes X-linked Early Onset Low-Turnover Osteoporosis

Abstract: Genetic factors play an important role in the development of osteoporosis. Several monogenic forms of osteoporosis have been recognized, most recently an X-chromosomal form resulting from mutations in the gene encoding plastin 3 (PLS3). PLS3 is a protein involved in actin bundle formation in the cytoskeleton. We present a large family with early onset osteoporosis and X-linked inheritance. Phenotyping was performed on 19 family members and whole-exome sequencing on 7 family members (5 with a diagnosis of early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
114
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(128 citation statements)
references
References 35 publications
(65 reference statements)
13
114
0
Order By: Relevance
“…The authors evaluated transiliac bone biopsies from 2 of them and saw evidence of low osteoid maturation time, suggesting that Plastin 3 could be involved in the mineralization process. The authors also described a low amount of trabecular bone but with a normal lamellation pattern, which is in accordance with what Laine et al [41] reported from bone biopsies of 5 patients with PLS3 mutations.…”
Section: Pls3: a Gene With Unknown Functionsupporting
confidence: 79%
See 2 more Smart Citations
“…The authors evaluated transiliac bone biopsies from 2 of them and saw evidence of low osteoid maturation time, suggesting that Plastin 3 could be involved in the mineralization process. The authors also described a low amount of trabecular bone but with a normal lamellation pattern, which is in accordance with what Laine et al [41] reported from bone biopsies of 5 patients with PLS3 mutations.…”
Section: Pls3: a Gene With Unknown Functionsupporting
confidence: 79%
“…Extraskeletal features that are often associated with OI such as blue sclerae, discolored teeth, joint hyperlaxity or short stature, are usually absent. To date, only 8 families with childhood-onset primary osteoporosis due to PLS3 mutations have been described, and the majority of the severely affected individuals are males [36,40,41]. Due to its location on the X chromosome, males have only one copy of PLS3 , which explains why males can present with a more severe phenotype than females.…”
Section: Pls3 Mutations: a Male Kind Of Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, SNVs and deletions in PLS3 have already been reported in patients with osteoporosis (39)(40)(41)(42)(43). Recently, some patients with PLS3 deletions have been described, and apart from severe osteoporosis there is a bone mineralization defect (42).…”
Section: Discussionmentioning
confidence: 99%
“…Further reports have supported a causative role for PLS3 mutations in the genesis of X-linked osteoporosis (48,49). While the biological role of PLS3 in bone is still largely unknown, a disturbance in osteocyte mechanosensing has been proposed as a putative mechanism based on animal model observations (16).…”
Section: Candidate Genes Identified Through Extreme Cases Of Osteopormentioning
confidence: 99%